5(x-8)+x=6(x-8)+8

Simple and best practice solution for 5(x-8)+x=6(x-8)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-8)+x=6(x-8)+8 equation:


Simplifying
5(x + -8) + x = 6(x + -8) + 8

Reorder the terms:
5(-8 + x) + x = 6(x + -8) + 8
(-8 * 5 + x * 5) + x = 6(x + -8) + 8
(-40 + 5x) + x = 6(x + -8) + 8

Combine like terms: 5x + x = 6x
-40 + 6x = 6(x + -8) + 8

Reorder the terms:
-40 + 6x = 6(-8 + x) + 8
-40 + 6x = (-8 * 6 + x * 6) + 8
-40 + 6x = (-48 + 6x) + 8

Reorder the terms:
-40 + 6x = -48 + 8 + 6x

Combine like terms: -48 + 8 = -40
-40 + 6x = -40 + 6x

Add '40' to each side of the equation.
-40 + 40 + 6x = -40 + 40 + 6x

Combine like terms: -40 + 40 = 0
0 + 6x = -40 + 40 + 6x
6x = -40 + 40 + 6x

Combine like terms: -40 + 40 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 11x+29y=-13 | | n+7n/5=72 | | 5x+15-4x=-6-12 | | 3/x=13/5x+2 | | 15w^3+14w^2-8w=0 | | -18-6k=6(1+2k) | | 17x=16x-24 | | 7(2x+3)=7 | | 5y+2(y-2)=7y-2(y-10) | | 17x=16x | | x/12=x/4-2 | | E=lR | | 44=-u+188 | | 18x+64=19x | | x/5=x/6-3 | | 0x^2-71x-9=0 | | 106=161-w | | 4x^2-13x+3x=0 | | (15/x)=((x^2)-7x+17) | | -v+111=202 | | 1/3+7/8+4/5 | | -x+279=208 | | 3x-6(x+1)=-3x+19 | | 21/5(-13/4p+5)=651/5 | | X(6x-3)=(6x+9)(x-8) | | -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 | | 26x+12=5(5x+4) |

Equations solver categories